(untitled) (Proceedings of the International Conference on Sustainable Management for Peace and Harmony, 2025)
This case study investigates BigBasket’s strategic shift toward offline retail channels as a response to declining customer base and increased competition in the online grocery sector. The research analyzes the rationale behind BigBasket’s omnichannel expansion, examining how the company aims to leverage physical presence to complement its digital platform and recover market position. The study evaluates the effectiveness of BigBasket’s offline initiatives including neighborhood stores, pickup points, and partnerships with traditional retailers in addressing customer acquisition and retention challenges. Through systematic analysis of customer behavior data, sales performance metrics, and market response indicators, the research assesses whether offline expansion can successfully reverse the declining customer trends. The case explores the operational challenges and opportunities associated with integrating offline and online channels, including inventory management, customer experience consistency, and cost optimization. The findings provide insights into the viability of omnichannel strategies for pure-play online retailers facing market saturation and competitive pressure. The study offers valuable lessons for e-commerce companies considering offline expansion as a growth and recovery strategy.